Health help‐seeking by men in Brunei Darussalam: masculinities and 'doing' male identities across the life course. Issue 6 (25th March 2019) - Idris, Deeni R.; Forrest, Simon; Brown, Sally
Abstract: Using data collected through semi‐structured interviews and focus group discussions with 37 adult men living in Brunei Darussalam, this paper explores how masculinities and expectations about male roles across the life course influence men's perceptions, of and attitudes towards health and health help‐seeking behaviour. Bruneian men gave accounts that consistently spoke of a series of masculine roles and associated attributes and behaviours, which mapped across the life course. Men described health and the steps that they had taken to protect their health in terms of responsibilities associated with being a breadwinner, provider of support for parents, role model and leader of the family. Whilst adherence to Bruneian norms about masculinity could obstruct men's engagement with health help‐seeking, we also found that men mobilised their understanding of Bruneian masculinity such that it provided culturally legitimate way of engaging in health help‐seeking. We conclude by considering implications for further development of conceptualisations of masculinities, particularly responding to the call to consider Connell's theory of 'hegemonic masculinity' in the context of the Global South. We also consider the implications of the findings of this research for policy and practice in provision of health promotion and services in Brunei.